Fadiga no trabalho de pilotos: uma psicologia sistêmica da aviação civil - Celestino, Victor Rafael Rezende (2017)
The overall objective of the research was to investigate validity evidences of fatigue measure at work of civil aviation pilots by means of the feeling of fatigue scale, adherent to the systemic approach of psychology. Feeling of fatigue is an emotion associated with a psychophysiological state of fatigue. In addition to this, the specific objectives were: to propose and evaluate a methodological adaptation for data and methods triangulation in an integrative review; to contrast and reorganize the knowledge about the subjective measurement of fatigue at work; and to introduce a proposal for systemic aviation psychology, in order to contribute to the mitigation of human fatigue risk. This thesis was developed in the model format of a collection of articles. From the perspective that the systemic psychology research occurs in interdisciplinary context, and it contrasts globally, this work proposes an innovative methodology of triangulation to synthesize and discuss the available knowledge on the subject. This methodology is applied in an integrative review to synthesize qualitative and quantitative convergent data, among workers subject to work in shifts in order to reorganize the knowledge about the measure of fatigue with the feeling of fatigue scale. The results include a systemic meta-model of the phenomenon of fatigue and showed the psychometric validity of the scale. Then, the work describes the prevalence of fatigue at work among Brazilian civil aviation pilots, and demonstrates the validity of the feeling of fatigue scale in this context, from the perspective of systemic psychology. In order to do this, a crosssectional type study was conducted, in a sample of 1,066 Brazilian airline pilots. The results showed the psychometric validity of the scale, suggesting a prevalence of fatigue at work of Brazilian airline pilots of 59.4% (female) and 64.1% (male), with an average of fatigue at work above a cut-off that would define workers as fatigued. Finally, the systemic perspective suggests that one cannot reduce the causes of fatigue, being necessary to consider the context and the systemic mediation of symptoms associated. The study confirms that, in civil aviation, the feeling of fatigue is a valid measure of the nature and the level of fatigue at work, which can be assessed (screening) by means of the scale.